Hooked how to build habit-forming products - Eyal, Nir (Portfolio/Penguin, 2014)
Why do some products capture widespread attention while others flop? What makes us engage with certain products out of sheer habit? Is there a pattern unlying how technologies hook us? Nir Eyal answers these questions (and many more) by explaining the Hook Model - a four-step process embedded into the products of many successful companies to subtly encourage customer behavior. Through consecutive "hook cycles," these products reach their ultimate goal of bringing users back again and again without depending on costly advertising or aggressive messaging. Hooked is based on Eyal's years of research , consulting, and practical experience. He wrote the book he wished had been available to him as a start-up founder - not abstract theory, but a how-to guide for building better products. Hooked is written for product managers, designers, marketers, start-up founders, and anyone who seeks to understand how products influence our behavior. -- from dust jacket.